Flexible investment decisions in the European interconnected transmission system - Blanco, G. (2011)
Investment decisions in the power transmission system are vulnerable to substantial long-term uncertainties. Especially, in large interconnected power systems like in Europe, the impact of different influencing factors on the decision-making process is hard to estimate. In the presented approach, stochastic simulations incorporate uncertainties like the development of fuel costs and demand growth. The resulting operation plan of the available power plants and the respective utilization of the transmission network are obtained by calculating the (least-cost) optimal power flow. The performance of possible network upgrades in uncertain scenarios is evaluated by applying a real options approach based on Monte Carlo simulations. The focus of the presented work is on the strategic flexibility that FACTS devices can offer in order to appropriately cope with the uncertain development of the future. A case study for the cross-border connection between Germany and the Netherlands shows the applicability and practicability of the presented approach.